Speak up, show up, and stand out : the 9 communication rules you need to succeed - Malandro, Loretta A. (McGraw-Hill, 2015)
"This lean and effective guide isn't just about choosing the right words; it's a whole new way of communicating to achieve unparalleled success. It offers the tools and skills readers need to build influence, deliver results, and significantly increase their communication effectiveness."--